Peran CSR PT.Pelindo 1 Belawan Dalam Meningkatkan Kesejahteraan Masyarakat di Lingkungan Perusahaan - M. Luthfi Arif Pratama; Azhari Akmal Tarigan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
Corporate social responsibility is increasingly implemented in line with companies' growing awareness of ethics and transparency in their business operations, so they believe that social responsibility can be a true form of corporate responsibility. Stakeholders must be communicated not only about the implementation of social responsibility activities, but also about social responsibility programs. because in addition to being a form of transparency, it also makes the program social and creates mutual understanding with all stakeholders. The purpose of this study is to see the role and impact of PT CSR. PELINDO in improving the well-being of the surrounding community. The research method used is descriptive qualitative. Research results show that the communication role implemented by PT. Pelindo 1 was effective enough to approach the community. The impact of their CSR program is also enough to help the community improve its economy, but the program they provide is not sustainable or community-based, so it cannot be felt by all the communities around the company. In addition to that, it realizes social responsibility by carrying out relief activities such as meeting the basic needs of the society, mass circumcisions, cataract treatment and compensation of orphans.